Kadar Testosteron dan Apoptosis pada Sel Penis dan Prostat dengan Pemberian Buceng - Taufiqurrachman Taufiqurrachman (MEDIA MEDIKA INDONESIANA, 2012)
Increase in testosterone levels and decrease in number of apoptosis in penis and prostate cells by buceng treatmentBackground: Apoptosis is an important biological mechanism in aging process, vitality, and declining of physiological function. Buceng has been traditionally used to delay aging and enhance male vitality. Administration of buceng to enhance Te concentration and decrease apoptosis in penis and prostate cells has not been elucidated. This study is to elucidate the effect of buceng on increase Te concentration and declining of apoptosis in penis and prostate cells of male Sprague Dawley rats.Method: Post test only control group design, 60 male of 90 days old Sprague Dawley rats and ± 300 gram body weight, has been assigned multistage randomly into four group. Group A, the castrated rats, treated with 50 mg buceng. Group B, the rats were not castrated, immediately sacrificed as a positive control. Group C, the castrated rats, got 2 mL of water, as a negative control. Group D, the castrated rats, treated with 6.75 mg mesterolon diluted in water. Manova statistical model was adopted to analyze the difference consentration of Te and apoptosis among groups. Analysis was perfomed by SPSS 13 with 95% confident interval.Result: Manova analysis by Wilk Lambda procedure in four groups indicated that Te concentration, apoptosis in penis and prostate cells among groups were significantly different (p=0.000).Conclusion: This study concludes that the administration of 50 mg buceng for 30 consecutive days could enhance Te concentration and decrease apoptosis in penis and prostate cells.Keywords: Buceng, apoptosis, vitality ABSTRAKLatar belakang: Apoptosis adalah mekanisme biologi penting dalam proses penuaan, penurunan vitalitas, dan penurunan fungsi fisiologis organ. Buceng telah dipakai secara tradisional untuk menghambat penuaan dan meningkatkan vitalitas pria. Efek buceng terhadap peningkatan kadar testosteron (Te) dan penurunan apoptosis sampai sekarang masih belum dibuktikan. Tujuan dari penelitian ini adalah untuk mengungkap efek buceng terhadap peningkatan kadar Te dan penurunan apoptosis sel penis dan prostatpada tikus jantan Sprague Dawley.Metode: Post test only control group design dengan sampel 60 tikus jantan galur Sprague Dawley umur 90 hari dengan berat badan (BB) ±300 gram, dibagi menjadi 4 kelompok secara multistage random masing-masing terdiri dari 15 ekor (ditentukan menurut formula Federer). Kelompok A, tikus dikastrasi, diberi buceng aa 50 mg. Kelompok B, tikus tanpa dikastrasi, langsung dimatikan, sebagai kontrol positif. Kelompok C, tikus dikastrasi, diberi akuades 2 mL, sebagai kontrol negatif. Kelompok D, tikus dikastrasi,diberi mesterolon 6,75 mg yang dilarutkan dalam air. Analisis statistik untuk menguji perbedaan kadar Te dan apoptosis adalah uji Manova. Semua analisis dilakukan dengan metode SPSS 13, dengan tingkat kepercayaan 95%.Hasil: Analisis Manova dengan prosedur Wilk lambda, pada empat kelompok menunjukkan bahwa kadar Te, apoptosis pada sel penis dan prostat di antara kelompok berbeda bermakna (p=0,000).Simpulan: Penelitian ini menyimpulkan bahwa pemberian buceng 50 mg selama 30 hari berturut-turut dapat meningkatkan kadarTe dan penurunan apoptosis pada sel penis dan prostat.